ALKALINE AND ACID METASOMATIC ROCKS IN GNEISS-AMPHIBOLITE COMPLEXES OF THE URALS: A CASE HISTORY OF THE UFALEI METAMORPHIC BLOCK, SOUTHERN URALS - Koroteev V.A.; Ogorodnikov V.N.; Sazonov V.N.; Polenov Yu.A. (My University, 2007)
The realization of the project “The Industrial Urals–the Polar Urals” requires assessment of the northern segment of the Urals for mineral resources related to the lithotectonic complexes formed in different geodynamic settings. In this connection, we have to assess mineragenic specialization and practical implications of widespread gneiss–amphibolite complexes. Thereby, primary attention should be focused not on the rock complexes but on the suture zones that control virtually all ore and nonore deposits and occurrences.